Intracranial blastomycosis mimicking high-grade neoplasm on magnetic resonance imaging and spectroscopy - Dhiraj Baruah; Saurabh Guleria; Michelle A. Michel; Sonia Gill (Indian Journal of Neurosurgery)
We describe a case of posterior fossa blastomycosis in an immunocompetent patient that mimicked high-grade neoplasm on neuroimaging. Histological analysis confirmed blastomycosis. Because the neuroimaging characteristics of intracerebral blastomycosis can be confused for neoplasm, these lesions must be confirmed histologically before initiating aggressive treatment for presumptive high-grade neoplasm. To our knowledge, it is the first description of a neoplasm mimic on MRS in the setting of intracranial blastomycosis.